A Study on Leadership Styles in SMEs - Mohd Khairuddin Hashim; Sa'ari Ahmad; Mustafa Zakaria (Universiti Sains Islam Malaysia, 2024)
The literature emphasizes on the importance of leadership to organizations. The review of the literature however indicates limited studies have attempted to empirically examine leadership in the context of small and medium-sized enterprises (SMEs). Despite the importance of leadership, a review of past studies suggests few studies have attempted to investigate leadership styles adopted by owners and managers of SMEs, particularly in the local context. This study attempted to examine the leadership styles practiced by SMEs. By using the Leadership Style Inventory (LSI), the study collected data from 140 owners and managers of SMEs. The results indicate that the owners and managers of the SMEs in the study followed four types of leadership styles that include supportive, logical, commanding and inspirational.